Development of Research and Community Service Roadmap of UNESA - Darni, Darni; Cahyaningrum, Sari Edi; Saksono, Lutfi; Nurhayati, Nurhayati (Proceeding Series of International Conference on Arts and Humanities, 2022)
The Surabaya State University (UNESA) is required to be able to independently manage institutions and be ready to innovate and collaborate with other institutions. The institutional and academic orientation has also experienced a paradigm shift from a teaching-based university to an entrepreneurial-based university. In the process towards independence, UNESA has prepared itself by compiling various documents required to become a State University with a Legal Entity (PTNBH). Research and community service activities are carried out in order to seek and find the truth through scientific methods in the fields of science, technology, or art for the advancement of science, technology, or art itself and the welfare of society. This study aims to produce the development of a road map document for research and community service (PKM) UNESA PTNBH. The main methods used to achieve this goal are reviewing documents related to research and community service, focus group discussions and workshops, and finalizing them. The resulting research outputs are UNESA PTNBH research and PKM roadmap documents and articles. The Technology Readiness Level (TKT) to be achieved at the end of this study is 3. The roadmap describes research and PKM plans from 2022-2045. There are 5 periods of time where the achievements are described in stages. Research is entirely based on innovation and commercialization (mass commercialization of innovative products) and also supports smart industry research and joint research with the world’s multi campuses. Whereas PKM in 2045 is described as achieving independence and partnerships that empower 3 UNESA flagships (Disabilities, Sports, Arts, and Culture).